DETERMINATION OF MERCURY AUTHORITY IN WATER, SEDIMENT, AND BLOT A WATER CAPUAS WATER WITH TECHNOLOGY AN NEUTRON ACTIVITY ANALYSIS (APN) - Yusman Wiyatmo; Bambang Ruwanto (Jurnal Penelitian Saintek, 2005)
The aim of this research were: 1) to determinate mercury disposition in water, sedimen,   and biota in Kapuas river, and 2)  to evaluate whether mercury disposition of the sample have been exceeded the threshold value which permitted  to  be  consummed  by animal an human. The sample of this research were water, sediment, and biota (algae and fish)  in Kapuas river.The research was carried out by experiment with  neutron activation  analysis  (NAA) method     The determination of the elements in sample was conducted by gamma spectroscopy.  The mercury disposition in sample was determined by comparing the cps of sample and the cps of standard (20 ppm). The results showed that the mercury disposition in water at TPI pier, KPLP pier, Dephub pier, and Kampung Mendawai were 0,25 ppm,0,14 ppm,    0,19 ppm,  and  0,09 ppm  respectively.    The mercury disposition at sediment in TPI pier and Dephub pier were 1.56 ppm0.63 ppm  respectively.  on  the  other  hand  the  disposition  of  the mercury in KPLP pier and Kampung Mendawai were not detectedThe mercury disposition at algae  in a  cross  of Pertamina   office, Taman Alun-Alun  Kapuas, Kapuas bridge, and near Sudarso hospital were 0,41 ppm, 0,59 ppm. 0.58 ppm, dan 0,68 ppm respectively.Keywords: The mercury disposition, water, sediment, water biota. andNAA.